CULTURAL APPROACH AS A PRIORITY DIRECTION OF THE EDUCATIONAL SYSTEM OF UZBEKISTAN - Safarova Roxat Gaybillaevna (Galaxy International Interdisciplinary Research Journal, 2022)
This article gives an idea of the possibilities of organizing the educational process based on cultural studies, the influence of culture on the student, the features of the content of education, the basic requirements for it, the possibility of creating a cultural environment in an educational institution.